Entrepreneurship education programmes research in Russia: Stakeholder expectations and university practice - А. A. Iashin; A. K. Klyuev; A. P. Bagirova; D. Williams (Russian State Vocational Pedagogical University, 2022)
Introduction. Entrepreneurial education, as an area of educational practice in higher education, is a relatively new area of activity for Russian universities. In this area, due to the special dynamics of development and transformation, especially in a pandemic, there is the most significant gap between the competencies formed by universities and in demand on the labour market. The rationale for the research stemmed from two major trends in the economy and society: industry demand for workforce with greater enterprise skills, at the same time a new generation, generation Z, seeks more flexible and more fulfilling career path. Therefore, to address these trends, universities have to diversify the skill set included in the academic curriculum.Aim. This study is aimed at studying the problems of interaction between universities and their stakeholders in curricula improvement.Methodology and research methods. Taken into consideration the regulatory nature of the curricula design in Russian Higher Education Institutions (HEIs) a two-step strategy has been adopted for this research. The first step was a concern with meta-analysis of the competencies outlined in Federal State Educational Standard (FSES) in Management through the lens of entrepreneurial competencies. The second step was to investigate inclusion of soft skills in entrepreneurship curricula in across Russian HEIs. To address the objective of research, descriptive statistics and non-parametric Mann-Whitney U-test were applied.Results. The research findings suggest in the environment where the degree programmes have to comply with set Governmental standards, curricula in entrepreneurship struggle to develop essential soft entrepreneurial skills. Most of the analysed curricula are heavily loaded with hard and cognitive skills. Even though the government proclaims a need for innovative development of the nation, creative and innovative thinking is not mentioned either in the FSES nor analysed curricula. The research findings also led to a surprising conclusion that very few core 'business' modules include the development of social or action-oriented skills in their learning outcomes.Scientific novelty. The scientific novelty of this study lies in the fact that for the first time the problems of ensuring the development of soft skills in entrepreneurial education in Russia have been studied.Practical significance. The results of the study will find their application in the design of entrepreneurial curricula to achieve the necessary balance of competencies in them.